Development aid and employment in the Federal Republic of Germany - Dieter Schumacher (Intereconomics, 1981)
The discussion on an increase of development aid is overshadowed by uneasiness about job opportunities at home. Against the demands for a sizeable increase of development aid funds it is often argued that such aid draws purchasing power away from the internal market if it is not tied to deliveries by the Federal Republic of Germany. Recent data show however that, since these “ties” were largely abolished in 1973, most funds allocated to development aid have still been flowing back into the Federal Republic in the shape of export orders.
Keywords: 330; Development Assistance